Sustainability practices and cost of capital: An empirical study of agricultural enterprises across global markets - Cui, Can (Edelweiss Applied Science and Technology, 2025)
This study explores how corporate sustainability and Environmental, Social, and Governance (ESG) performance are linked to the cost of capital in the financial markets of agricultural enterprises around the world. For the period from 2019 to 2024, a sample set of more than 1,200 agricultural enterprises from North America, Europe, and Asia-Pacific is examined using multiple regression to explore the role of ESG factors in shaping a company’s WACC. It was observed that for each additional point in the ESG composite score, WACC decreases by 0.035 percentage points. The impact varies by region, being strongest in European agricultural enterprises, somewhat less in North America, and mildest in Asia-Pacific. Based on the analysis, environmental considerations are found to significantly reduce WACC more than other factors. These data indicate that incorporating sustainability helps companies reduce costs and increase their value, confirming to managers and investors that sustainability can be a key strategy in agricultural enterprises. The paper concludes by outlining policies for change and proposing new research topics at the intersection of sustainability and corporate finance in agricultural enterprises.